Religie: hoeksteen of steen des aanstoots? - de Hart, Joep; Dekker, Paul (Religie & Samenleving, 2012)
The Netherlands is a religious tolerant country; the Dutch are not very inclined to pay attention to the belief of politicians, and increasingly they prefer politics and religion to be separated. The picture of the developments in the past decades is mixed: clearly increased doubts about unlimited freedom of religion, a small drop in support for religion as a guide to political action, and a virtually unchanged support for denominational education. These findings suggest a growing awareness of potential negative aspects of religion, a declining role of religion in peoples own lives, and a stable positive attitude towards pluralism. The Netherlands is not a country that is only populated by descendants of Calvin and Voltaire. Among the population there are believers and unbelievers in all shapes and sizes. Between the non church members and church members there are in many points clear differences, but these also exist, outside the churches, between philosophical not interested unbelievers, the adherents of holistic spirituality and solo-religious people, and in church circles between nominal members and regular church goers.